The Plasmodium falciparum Antigen MB2 Induces Interferon-γ and Interleukin-10 Responses in Adults in Malaria Endemic Areas of Western Kenya - Lyticia A Ochola; Gideon M Ng′wena; Gregory S Noland; Bartholomew N Ondigo; George Ayodo; Chandy C John (Journal of Global Infectious Diseases, 2013)
Background: MB2 is a novel Plasmodium falciparum antigen of unknown function expressed in pre-erythrocytic and blood stages of infection in the human host. Interferon-gamma (IFN-γ) and interleukin (IL)-10 responses to other P. falciparum antigens have been associated with protection from clinical malaria, but these responses have not been studied for MB2. The present study was undertaken to characterize IFN-γ and IL-10 responses to P. falciparum MB2 antigen in adults living in areas of differing malaria transmission in Western Kenya. Materials and Methods: Cytokine responses to two 9-mer MB2 peptides predicted to be human leukocyte antigen (HLA) class I restricted T-cell epitopes were measured by enzyme-linked immunosorbent assay (ELISA) (IFN-γ and IL-10) and enzyme-linked immunosorbent spot (ELISPOT) (IFN-γ) in adults (n = 228) in areas of unstable and stable malaria transmission. HLA class I restriction of responses was assessed in a sub-group of the study population. Results: IFN-γ and IL-10 responses to MB2 peptides by ELISA were observed in both sites with no significant difference in prevalence (IFN-γ, unstable transmission area, 18.8%, stable transmission area, 27.5%, P = 0.33; IL-10, unstable transmission area, 22.5%, stable transmission area, 25.0%, P = 0.78). Prevalence of IFN-γ responses by ELISPOT was also similar in both areas (unstable, 10.8%, stable, 10.9%, P = 0.98). Neither IFN-γ nor IL-10 responses showed evidence of HLA class I restriction. Conclusions: MB2 induces IFN-γ and IL-10 responses in adults living in both stable and unstable malaria transmission areas. Future studies should assess if these responses are associated with protection from clinical malaria.